1984
DOI: 10.1128/iai.45.3.558-560.1984
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio cholerae hemagglutinin/protease nicks cholera enterotoxin

Abstract: Unnicked cholera enterotoxin was isolated from culture supernatants of Vibrio cholerae 569B by either rapid processing of flask-grown cultures or by growing and processing fermentor cultures in the presence of ethylene glycol-bis(O-aminoethyl ether)-N,N,N',N'-tetra acetic acid, an inhibitor of the previously described V. cholerae hemagglutinin/protease. When unnicked cholera enterotoxin was incubated with purified hemagglutinin/protease, the unnicked A subunit was converted to a molecular weight consistent wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(45 citation statements)
references
References 12 publications
0
45
0
Order By: Relevance
“…Metalloproteases may also be related to virulence by activation of other extracellular toxins. This has been shown with proteases from Staphylococcus aureus and Vibrio cholerae (Drapeau 1978;Booth, Boesman-Finkelstein & Finkelstein 1984). However, activation of the lethal toxin (GCAT) is performed with the serine protease in A. salmonicida (Eggset et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Metalloproteases may also be related to virulence by activation of other extracellular toxins. This has been shown with proteases from Staphylococcus aureus and Vibrio cholerae (Drapeau 1978;Booth, Boesman-Finkelstein & Finkelstein 1984). However, activation of the lethal toxin (GCAT) is performed with the serine protease in A. salmonicida (Eggset et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The HA/P of V. chokrue 01 is recognized as a virulence factor in pathogenesis of cholera [14]. It has been reported that HA/P contributes to pathogenesis by degrading several physiologically important substances of host 1193, including mucin, fibronectin and secretory IgA, and by activating the cholera enterotoxin (CT) with nicking A subunit of the toxin [20]. Recently, Finkelstein et al [14] have reported HA/P works as detachase which facilitate detaching of the V. choterue organism from host epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Young and Broadbent reported the purification of three types of protease from V. cholerae O1: phenylmethylsulfonyl fluoride inhibitable type 1, metalloprotease and serine protease inhibitor resistant type II, and EDTA inhibitable type III [2]. Booth et al [3,4] reported that soluble HA/protease is a metalloenzyme that can be inhibited by a variety of chelating agents and inhibitors of zinc * Corresponding author. metalloprotease, and that it nicks cholera enterotoxin.…”
Section: Introductionmentioning
confidence: 99%